Unsupervised and Supervised Machine Learning in User Modeling for Intelligent Learning Environments - Amershi, Saleema; Conati, Cristina (In Proceedings of the ACM/SIGCHI Conference on Intelligent User Interfaces (IUI 2007), 2007)
In this research, we outline a user modeling framework that uses both unsupervised and supervised machine learning in order to reduce development costs of building user models, and facilitate transferability. We apply the framework to model student learning during interaction with the Adaptive Coach for Exploration (ACE) learning environment (using both interface and eye-tracking data). In addition to demonstrating framework effectiveness, we also compare results from previous research on applying the framework to a different learning environment and data type. Our results also confirm previous research on the value of using eye-tracking data to assess student learning.